2012
DOI: 10.1080/0020739x.2011.618560
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of factors impacting success for incoming college engineering students in a summer bridge program

Abstract: A summer bridge program for incoming engineering and computer science freshmen has been used at the University of Wisconsin-Milwaukee from 2007 to 2010. The primary purpose of this program has been to improve the mathematics course placement for incoming students who initially place into a course below Calculus I on the math placement examination. The students retake the university's math placement examination after completing the bridge program to determine if they then place into a higherlevel mathematics co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 10 publications
0
54
0
Order By: Relevance
“…Reisel says "the use of math ACT scores as a predictor of success in the program is reasonable, but should be used with caution" while studies by Hoffman and Lowitzki, Munro, and Zheng et al argue that high school GPA is more predictive than standardized test scores [14,31,32]. Foley-Peres and Poirier found that SAT scores were less important than placement test scores, and Ngo and Kwan indicated that multiple variables should be included when placing students in the initial math class [19,20].…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Reisel says "the use of math ACT scores as a predictor of success in the program is reasonable, but should be used with caution" while studies by Hoffman and Lowitzki, Munro, and Zheng et al argue that high school GPA is more predictive than standardized test scores [14,31,32]. Foley-Peres and Poirier found that SAT scores were less important than placement test scores, and Ngo and Kwan indicated that multiple variables should be included when placing students in the initial math class [19,20].…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Upon completion of the program students are enrolled in the appropriate math course for the fall semester based on their summer performance. This allows students to start at the appropriate level of math that will best support a strong math foundation going forward [1]. As a result of strong math performance over the summer, students may earn the opportunity to bypass remediation math courses that may otherwise be dictated by their Math ACT Sub Score.…”
Section: Alliance Of Strategic Partnershipsmentioning
confidence: 99%
“…Some of these programs are purposed to close the achievement gaps of underrepresented minority (URM) students pursuing engineering degrees as compared to non-minority students. URM in the sciences or engineering is defined as a student who has self-identified as Black or African American, a Hispanic, or American Indian/Alaskan [1]. Summer bridge programs vary per institution and can be structured to offer different types of experiences for participants.…”
Section: Introductionmentioning
confidence: 99%
“…Students who attend an on-campus, summer bridge program have been shown to have greater success and persistence in part due to the ability to form a cohort and gain familiarity with campus resources [18][19][20] . Elements such as study centers, course clustering, tutoring and structured study groups that foster collaborative learning have been found to promote student success for underrepresented students [21][22][23] .…”
Section: K-12 Programsmentioning
confidence: 99%